TO EXAMINE OF 8TH GRADE STUDENTS’ CONDITIONS IN THE CONTEXT OF NON-ROUTINE PROBLEM IN TERMS OF TOOL/OBJECT DIALECT AND CHANGE OF FRAMEWORK - Sevilay TAVŞAN (Fırat University, 2019)
The purpose of this study is to examine 8th grade students' conditions in the context of non-routine problem in terms of tool / object dialect and change of framework. The study was conducted in a state secondary school in the province of Trabzon. The study group consists of three students selected by the "homogeneous sampling" method. Two of these students are girls and one is a boy. The study was designed from the qualitative research approach to the "case study" design. Non-routine problem solving activity and video recorder were used as data collection tool. The solution process of the students was analyzed in two different ways, using the explanations of Douady (1986). In the first phase of the analysis, if a concept was used in solving a problem, it was considered as a “tool”; if the concept was not used in problem solving but it was considered as a general definition it was evaluated as an “object”. Secondly, in problem solutions of the students; it was treated as “algebraic framework”, which uses unknown and algebraic operations; as an “arithmetic framework” by performing only numerical operations without useing any unknown, and as an “analytical framework” by using the cartesian coordinate system. According to the findings obtained, during the application process of the students; it has been seen that they have used mathematical tools such as four operations (addition, subtraction, multiplication and